Mechanism of action of cordycepin in the treatment of hepatocellular carcinoma via regulation of the Hippo signaling pathway - Xiaomin Li; Qing Liu; Songyu Xie; Xiaoping Wu; Junsheng Fu (Food Science and Human Wellness, 2024)
Hepatocellular carcinoma (HCC) is one of the common most malignant tumors. This study aimed to determine the in vitro and in vivo anticancer activity of cordycepin and elucidate its mechanism of action. The results of in vitro and in vivo studies revealed that cordycepin inhibited proliferation and migration in HepG-2 cells and inhibited the growth of HepG-2 xenograft-bearing nude mice by inducing apoptosis. Transcriptome sequencing analysis revealed a total of 403 differential genes, which revealed that cordycepin may play an anti-HCC role by regulating Hippo signaling pathway. The regulatory effects of cordycepin on the Hippo signaling pathway was further investigated using a YAP1 inhibitor. The results demonstrated that cordycepin upregulated the expression of MST1 and LAST1, and subsequently inhibited YAP1, which activated the Hippo signaling pathway. This in turn downregulated the expression of GBP3 and ETV5, and subsequently inhibited cell proliferation and migration. Additionally, YAP1 regulated the expression of Bax and Bcl-2, regulated the mitochondrial apoptotic pathway, and induced apoptosis by upregulating the expression of the caspase-3 protein. In summary, this study reveals that cordycepin exerts its anti-hepatocarcinoma effect through regulating Hippo signaling pathway, and GBP3 and ETV5 may be potential therapeutic targets for hepatocarcinoma.